Sequential Heterotrophy–Dilution–Photoinduction Cultivation of Haematococcus pluvialis for efficient production of astaxanthin. (December 2015) - Wan, Minxi; Zhang, Zhen; Wang, Jun; Huang, Jianke; Fan, Jianhua; Yu, Anquan; Wang, Weiliang; Li, Yuanguang
Highlights: SHDP can be applied effectively in the production of astaxanthin from H. pluvialis. DCW of 26 g/L and productivity of 64.1 mg/L/h were obtained in heterotrophy stage. Cells accumulated considerable astaxanthin up to 4.6% of DCW. Outdoor experiments showed the application feasibility of SHDP. Abstract: A novel cultivation strategy called "Sequential Heterotrophy–Dilution–Photoinduction" was successfully applied in the cultivation of Haematococcus pluvialis to produce astaxanthin effectively. Cells were first cultivated heterotrophically to achieve a high cell density, then were diluted to a suitable concentration and switched to a favorable environment for cells acclimation. Finally, the culture was transferred to high light environment for astaxanthin accumulation. By this strategy, the dry cell weight of 26 g/L and biomass productivity of 64.1 mg/L/h were obtained in heterotrophy stage which surpassed ever before reported in literatures. Meanwhile, the cells could accumulate considerable astaxanthin up to 4.6% of dry cell weight after 10 days of photoinduction. Furthermore, the application prospects of the strategy were confirmed further by outdoor experiments. Therefore, this novel strategy provided a promising approach for high-efficient production of natural astaxanthin from H. pluvialis to meet the huge demand of this high value product.